Bias in Beta values and its Correction:Empirical Evidence from the Jakarta Stock Exchange - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This study concerns with the issue that beta values in the emerging capital markets are biased, due to nonsynchronous trading activities. This study COT1 f the issue, and gives evidences that beta values of firms listed in the Jakarta Stock Exchange (JSX) are biased. The bias steeds to be corrected. From the three methods employed: the Scholes and Williams ( 1977), the Dimson ( 1979), and the Fowler and Rorke (1983). The latter is the strongest in reducing the bias. This study also finds that the bias in beta values is strengthened by the return data that are not normally distributed. By normalizing the distribution of the return data, the correction of the bias is quicker. For return data then' are not normally distributed, the correction of the bias needs longer period (four lags alidfourleads)adjustment, while fornornrallydistributed return data, the correction only needs one lag and one lead period adjustment.